Quadratic formula
in Algebra 2 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

6m²-8m-12=0,

so 3m²-4m-6=0,

m²-(4/3)m-2=0, m²-(4/3)m=2,

m²-(4/3)m+4/9=2+4/9=22/9,

(m-⅔)²=22/9,

m-⅔=±√22/3,

m=⅔±√22/3=⅓(2±√22)=2.23 or -0.90 approx.

The quadratic formula gives the same result:

m=(4±√(4²+4×3×6))/6=(4±√(16+72))/6=

(4±√88)/6=(2±√22)/3.

by Top Rated User (716k points)

Related questions

0 answers
asked Feb 12, 2013 in Algebra 1 Answers by anonymous | 158 views
1 answer
asked Apr 23, 2013 in Geometry Answers by anonymous | 123 views
1 answer
asked Sep 5, 2019 in Algebra 1 Answers by kyle | 33 views
2 answers
asked Nov 17, 2014 in Algebra 1 Answers by anonymous | 1.1k views
1 answer
asked Feb 13, 2013 in Algebra 1 Answers by anonymous | 113 views
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,489 questions
89,399 answers
1,998 comments
8,081 users